2020
DOI: 10.1371/journal.pone.0229521
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and mechanical ventilation impede the functional properties of resident lung mesenchymal stromal cells

Abstract: Resident/endogenous mesenchymal stromal cells function to promote the normal development, growth, and repair of tissues. Following premature birth, the effects of routine neonatal care (e.g. oxygen support and mechanical ventilation) on the biological properties of lung endogenous mesenchymal stromal cells is (L-MSCs) is poorly understood. New Zealand white preterm rabbits were randomized into the following groups: (i) sacrificed at birth (Fetal), (ii) spontaneously breathing with 50% O 2 for 4 hours (SB), or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“… [133] In vitro , LRMSC from patients with BPD and hyperoxia-impaired LRMSCs facilitates myofibroblast phenotype conversion and leads to fibrotic reorganization. [116 , 125] Taken together, the above findings reveal LRMSC function heterogeneity under distinct settings of lung injuries. Further in vitro and in vivo studies recapitulating their spatial location and molecular and functional properties are needed to enrich our understanding of LRMSCs, thus improving autologous therapies for lung diseases.…”
Section: Pulmonary Endogenous Stem Cellsmentioning
confidence: 71%
See 1 more Smart Citation
“… [133] In vitro , LRMSC from patients with BPD and hyperoxia-impaired LRMSCs facilitates myofibroblast phenotype conversion and leads to fibrotic reorganization. [116 , 125] Taken together, the above findings reveal LRMSC function heterogeneity under distinct settings of lung injuries. Further in vitro and in vivo studies recapitulating their spatial location and molecular and functional properties are needed to enrich our understanding of LRMSCs, thus improving autologous therapies for lung diseases.…”
Section: Pulmonary Endogenous Stem Cellsmentioning
confidence: 71%
“…LRMSCs also secrete critical biologic factors for lung growth and development, such as FGF-7, FGF-10, interleukin-8, VEGF, and angiopoietin-1. [116 , 125] Considerable evidence suggest their immune regulatory and inflammation inhibitory properties. [126] , [127] , [128] In sum, their regenerative capacity along with their secretory and anti-inflammatory functions paves a promising way for LRMSC-targeted cell therapy to halt lung diseases.…”
Section: Pulmonary Endogenous Stem Cellsmentioning
confidence: 99%
“…Regardless, these observed in utero alterations in essential cell populations, developmental factors and pulmonary morphology might render the preterm lungs more susceptible to sequential postnatal insults. Previously, it was shown that postnatal hits, including mechanical ventilation and oxygen supplementation, resulted in a decreased differentiation and proliferation potential in isolated lung endogenous stem cells ( 51 ). Postnatal cohort studies, using BPD and RDS samples, have also shown that preterm birth combined with common clinical practices, like oxygen supplementation and ventilation, resulted in decreased AEC2 and Club cell numbers, positive for TTF-1 ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were described in a study using New Zealand white preterm rabbits, whereby short-term hyperoxia (4 h with 50% oxygen) with mechanical ventilation altered the differentiation capacity of LR-MSCs. 78 After mechanical ventilation, the LR-MSCs exhibited lower adipogenic and osteogenic potentials. In addition, structural analysis using electron microscopy revealed LR-MSCs in the hyperoxia/mechanical ventilation group had evidence of cellular stress in the nucleus, smaller mitochondria, and distended endoplasmic reticula.…”
Section: Lung Resident Mscs In Pathogenesis Of Chronic Lung Diseasesmentioning
confidence: 98%